Assessing the acceptability of the health education program in Dengue prevention and control in Buon Ma Thuot city in Dak Lak province, Vietnam - Giang Huong Pham (Journal of Community Empowerment for Health, 2022)
Dengue fever is a serious human arboviral infection that globally spreads and is a top concern amongst health care professionals and governments including Vietnam. The best measure to prevent and control dengue is vector control which is supported by social mobilization and health education. This study assessed the acceptability of health education programs in dengue fever prevention and control for the first time in Dak Lak Province, which is located in the endemic area of dengue fever in Vietnam. This study was an implementation research with qualitative methods. Nine in-depth interviews and six focus group discussions involving thirty-four informants were conducted at province, district, and ward levels. The acceptability was analyzed based on the seven components of the Theoretical Framework of Acceptability. Thirty-four informants ranging from ages 26 to 54 years participated. All belonged to the delivering or receiving groups of the health education program. The years of experience of the delivering group were at least two years with the health education program in dengue prevention and control and all individuals in the receiving group participated in the program. Six components, namely affective attitude, perceived effectiveness, intervention coherence, ethicality, and self-efficacy, were coded in all transcripts. Meanwhile, none of the interviews mentioned the opportunity cost. Overall, the acceptability of the health education program in dengue fever prevention and control was considered to be positive. However, the transformation from education to behavior requires time for acceptance and the persistence of the education program. Besides, the major burden of the program was the limited budget that could lead to inadequate facilities for indirect communication and low human resources.